Effect of size and site preference of trivalent non-magnetic metal ions (Al3+, Ga3+, In3+) substituted for Fe3+ on the magnetostrictive properties of sintered CoFe2O4 - Anantharamaiah, P. N.; Joy, P. A. (Journal of Physics D-Applied Physics, 2017)
The influence of size and crystallographic site preference of three non-magnetic isovalent metal ions of larger (In3+), comparable (Ga3+) and smaller (Al3+) sizes, substituted for Fe3+ in the spinel lattice of CoFe2O4 on its magnetostrictive properties is compared. For the different compositions in CoFe2-xMxO4 (M = In3+, Ga3+, Al3+ and 0 <= x <= 0.3), significant changes in the structural and magnetic parameters are observed with the degree of substitution, due to the size and site preferences. Magnetic and Raman spectral studies revealed that Al3+ is substituted for Fe3+ at both octahedral and tetrahedral sites for all compositions, whereas In3+ and Ga3+ are substituted for Fe3+ at the tetrahedral site only for x <= 0.2 and partly at the octahedral site for x > 0.2. Regardless of the differences in the ionic size, site preference and the magnetic properties, compositions in all three series with x = 0.1 showed almost equal magnitude of maximum magnetostriction (lambda(max) = similar to 230 ppm), marginally higher than that of x = 0 (217 ppm). However, at higher substituted compositions, lambda(max) is decreased with x, but the decrease is much faster for the Al-substituted compositions. The maximum strain sensitivity, [d lambda/dH](max), is also found to be comparable for all three compositions. The comparable magnetostriction characteristics and high strain at low magnetic fields for different substituted compositions at low levels of substitution are attributed to the local structural distortions associated with the inhomogeneous distribution of the substituted ions in the spinel ferrite lattice. The studies suggest ways to optimise the magnetostriction properties of properly substituted sintered cobalt ferrite for applications in sensors and actuators.

Enhanced strain sensitivity in magnetostrictive spinel ferrite Co1-xZnxFe2O - Bhame, Shekhar D.; Joy, P. A. (Journal of Magnetism and Magnetic Materials, 2018)
We report the magnetic and magnetoelastic properties of spinel oxide system Co1-xZnxFe2O4 (CZF series) where x = 0.0, 0.1, 0.2, 0.3, 0.4, and 0.5. All the composition were prepared by conventional solid state synthesis method and exhibited pure spinel phase formation. The lattice parameters showed gradual increase indicating uniform distribution Zn ions in cobalt ferrite lattice. The magnetic properties such as saturation magnetization and coercive field were drastically affected with Zn substitution showing enhanced saturation magnetization and a sharp decrease in the coercivity. The room temperature magnetostrictive properties showed a promising 30% enhancement in the slope of magnetostriction curve for x = 0.2 composition and a reasonable magnetostrictive strain of 110 ppm indicating its suitability as a promising magnetostrictive material. (c) 2017 Elsevier B.V. All rights reserved.

Effect of co-substitution of Co2+ and V5+ for Fe3+ on the magnetic properties of CoFe2O4 - Anantharamaiah, P. N.; Joy, P. A. (Physica B: Condensed Matter, 2019)
Different chemical compositions in Co1+2xVxFe2-3xO4 (0 ≤ x ≤ 0.1) have been synthesized by the conventional solid-state reaction method and processed under identical conditions. The materials are investigated to assess the impact of change in the oxidation states of metal ions on structural and magnetic properties of cobalt ferrite. Rietveld refinement of the X-ray diffraction patterns revealed a single phase nature of all compositions with cubic spinel structure. The cubic lattice parameter was found to decrease non-linearly from 8.393 Å for x = 0 to 8.377 Å for x = 0.1, due to the effect of ionic size and valency of the substituted metal ions. Sintered co-substituted compositions exhibited smaller grains against unsubstituted counterpart, due to low melting point of raw material V2O5. Strong experimental evidence of V substitution for Fe at the tetrahedral sites of the spinel ferrite has been extracted from the Raman spectral analysis. Saturation magnetization (Ms) was observed to decrease from 452 kA/m for x = 0–411 kA/m for x = 0.1. Coercivity (Hc) and magnetocrystalline anisotropy (K1) were also found to follow the same trend. Variation of the structural and magnetic parameters is attributed to the changes in the oxidation state of Co from 2 + to 3 + as it is confirmed from the results of XPS analysis.